Sardinia and the Byzantine West Paradigm Shifts and Changing Perceptions - Muresu, Marco (Studia Ceranea, 2024)
The paper focuses on Sardinia from the fall of Carthage (698) to the rise of its autonomous rulers, the iudikes, in the mid-9th c. During these centuries, the island managed to convey a sense of historical standing between different ‘worlds’: the Latin West, the Byzantine empire, and the Muslims in North Africa and Spain. Albeit traditionally considered as a proof of ‘periphery’ and ‘isolation’, Sardinia’s insularity condition and its development as an unconquered liminal polity among the major powers in the Western Mediterranean received renewed interest through the re-assessment of the archaeological, sigillographic and numismatic record. As such, the paper is an account of the key features of this transition and offers new perspectives on the island’s resilience within the formative phases of a Medieval Mediterranean that we increasingly understand in terms of its connectivity.